CENPF as a Potential Biomarker Associated with the Immune Microenvironment of Renal Cancer - Meilin Chen MS; Xiuxin Tang MS; YanPing Liang MD; Tangdang Ding MS; Meifang He PhD; Dong Wang PhD; Ruizhi Wang PhD (Technology in Cancer Research & Treatment)
Introduction Renal cancer, particularly Kidney Renal Clear Cell Carcinoma (KIRC), remains a major clinical challenge due to its aggressive nature and poor prognosis. Identifying reliable biomarkers for tumor progression and survival is critical for improving patient outcomes. This study aimed to investigate the role of Centromere Protein F (CENPF) as a potential prognostic biomarker for renal cancer. Method Data from the TCGA database, including Kidney Chromophobe (KICH), Kidney Renal Papillary Cell Carcinoma (KIRP), and KIRC, were analyzed to identify differentially expressed genes. Molecular Complex Detection (MCODE) was used to identify significant gene modules among upregulated genes, and univariate Cox regression analyses assessed the prognostic value of hub genes. Retrospective qPCR was conducted on tissue and plasma samples from KIRC patients to validate findings. Single-cell sequencing data from the GSE159115 dataset were analyzed, and the CIBERSORT algorithm was applied to evaluate the composition of tumor immune infiltrating cells (TIICs). Results CENPF was identified as a hub gene significantly upregulated in renal cancer subtypes, with overexpression linked to worse survival outcomes in KIRC patients. Retrospective qPCR confirmed high CENPF expression was associated with poorer prognosis. Single-cell sequencing revealed that CENPF is predominantly expressed in T-cell clusters. TIIC analysis showed a negative correlation between CENPF and resting mast cells, but positive correlations with follicular helper T-cells and memory-activated CD4T-cells. Prognostic analysis indicated that high follicular helper T-cell expression predicted poorer survival, while high plasma cell expression correlated with better outcomes. Conclusion CENPF plays a critical role in tumor progression and the modulation of the tumor immune microenvironment in KIRC. These findings suggest that CENPF could serve as a valuable prognostic biomarker and potential target for therapeutic intervention in renal cancer.